2005
DOI: 10.1177/1094670505276683
|View full text |Cite
|
Sign up to set email alerts
|

A TRIZ-Based Method for New Service Design

Abstract: This article demonstrates the viability of applying the theory of inventive problem solving (TRIZ) to services by proposing a new approach to new service design. Traditionally, the effectiveness of new service design is unpredictable as service design relies largely on inspiration and the past experiences of service designers. By integrating TRIZ problem-solving tools and its knowledge base, the authors propose a new TRIZ-based approach to address this weakness in service design. Through two case studies, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
133
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 29 publications
0
133
0
Order By: Relevance
“…Sources: (Berkley 1996, Tax and Stuart 1997, Johne and Storey 1998, Botschen et al 1999, Edvardsson et al 2000, Bullinger et al 2003, Gustafsson and Johson 2003, Chai et al 2005, Johann and Kurt 2007, Kuo 2008, Kung 2008 …”
Section: Table 3 Techniques and Methods Adopted By The S-a Framework mentioning
confidence: 99%
“…Sources: (Berkley 1996, Tax and Stuart 1997, Johne and Storey 1998, Botschen et al 1999, Edvardsson et al 2000, Bullinger et al 2003, Gustafsson and Johson 2003, Chai et al 2005, Johann and Kurt 2007, Kuo 2008, Kung 2008 …”
Section: Table 3 Techniques and Methods Adopted By The S-a Framework mentioning
confidence: 99%
“…• Some companies declare that if their customers are not satisfied with their products or services, they can get their money back (Chai et al, 2005) b) Have a support plan to control the harmful effects and raise the positive effect of the service.…”
Section: Preliminary Anti-action (Prior Counteraction)mentioning
confidence: 99%
“…Different studies have used several TRIZ IPs tools to help a problem solver find solutions for service system contradictions. Chai, Zhang, and Tan (2005) developed a model for creating new services based on TRIZ and they used the 40 IPs to predict solutions using two case studies. Lin and Su (2007) reported that 39 parameters formed a contradiction matrix and 40 IPs can be used in the service sector to identify solutions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory examines the challenges about the problems where innovation is needed. This theory applied in different categories of industries, including process development [13,14], eco-innovation [15], and service innovation (Table 1) [16]. …”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%